2019
DOI: 10.1183/23120541.00017-2019
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine use association with pulmonary diseases: a retrospective investigation of hospital discharges in California from 2005 to 2011

Abstract: BackgroundMethamphetamine can have acute and long-term adverse health consequences. Our objective was to determine whether methamphetamine use is associated with more hospitalisation codes for asthma exacerbation, chronic obstructive pulmonary disease (COPD) exacerbation, pneumonia and acute respiratory failure (ARF).MethodsThe Health Care Utilization Project (HCUP) database includes retrospective inpatient discharge abstracts from 2005 through 2011 from the California state inpatient databases (SIDs). ICD-9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…55 Tsai et al. 56 concluded that there are higher rates of pneumonia and acute respiratory failure in both men and women who abuse methamphetamine, whereas acute exacerbations of chronic obstructive pulmonary disease occurred more often in women. There was no link found between methamphetamine use and acute asthma.…”
Section: Medical Usementioning
confidence: 99%
“…55 Tsai et al. 56 concluded that there are higher rates of pneumonia and acute respiratory failure in both men and women who abuse methamphetamine, whereas acute exacerbations of chronic obstructive pulmonary disease occurred more often in women. There was no link found between methamphetamine use and acute asthma.…”
Section: Medical Usementioning
confidence: 99%
“…All of these may increase their vulnerability to COVID-19 infection [3][4][5]. Regular administration of METH is associated with various neurological symptoms such as anxiety, depression, psychosis, psychiatric impairment [6], cardiac [7], respiratory complications [8], and overall decreased immune health. METH users group, is much stigmatized and marginalized, and tend to remain well hidden in large population groups.…”
mentioning
confidence: 99%